Relative influences of cracking and connection yield on transverse distributions of moments and reactions in timber-concrete composites. (1st June 2021) - Mudie, J.; Sebastian, W.M.; Norman, J.; Bond, I.P.
Highlights: Multi-joist timber-concrete composites of various connection layouts were tested to failure. Both moment and reaction sharing were inferred across the full loading range. Cracking transformed support reaction sharing by a factor of up to 1.60. Connection yield transformed bending moment sharing by a factor of up to 1.62. Nonlinear FE models reliably predict load response and help elucidate TCC mechanics. Abstract: This paper uses tests backed up by nonlinear FE analysis for parametric study of transverse load sharing in large-scale timber-concrete composite (TCC) specimens, each comprising multiple hardwood LVL joists fastened to a single concrete slab via bonded-in, ductile steel mesh connectors. The study for the first time compares midspan moment sharing with support reaction sharing across the full range of behaviour up to failure for two distinct connection layouts, and it highlights the relative influences of connector yield and concrete cracking on the nonlinear load sharing characteristics. For the specific examples of this study, the results show that while cracking had little effect on transverse distribution of midspan moments, it did change the transverse distribution of support reactions by a factor of up to 1.60. Conversely, connection yield had little effect on transverse support reaction distribution, but it changed the transverse distribution of midspan moments by a factor of up to 1.62. Further, the test-verified FE analyses revealed that an inadvertent 20% drop in concrete tensile strength observed in the tests exacerbated support reaction sharing by up to 12.5%. These numbers approach or exceed the safety factors used in design. Wider studies are needed to determine practical bounds for these load sharing effects and to develop user-friendly means of allowing for these effects in design.